2015
DOI: 10.1121/1.4926561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phonetic production training with visual feedback on the perception and production of foreign speech sounds

Abstract: Second-language learners often experience major difficulties in producing non-native speech sounds. This paper introduces a training method that uses a real-time analysis of the acoustic properties of vowels produced by non-native speakers to provide them with immediate, trial-bytrial visual feedback about their articulation alongside that of the same vowels produced by native speakers. The Mahalanobis acoustic distance between non-native productions and target native acoustic spaces was used to assess L2 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 32 publications
10
86
1
Order By: Relevance
“…A comparison of the pre‐ and posttest revealed sound learning for the perception group, but not for the perception+production group. With the addition of feedback on concrete acoustic properties of the productions during training, however, Kartushina, Hervais‐Adelman, Frauenfelder, and Golestani () did find in a similar phoneme discrimination study that production training can be helpful for learning to discriminate L2 sounds.…”
Section: Interweaving Accent Production and Accent Comprehensionmentioning
confidence: 99%
“…A comparison of the pre‐ and posttest revealed sound learning for the perception group, but not for the perception+production group. With the addition of feedback on concrete acoustic properties of the productions during training, however, Kartushina, Hervais‐Adelman, Frauenfelder, and Golestani () did find in a similar phoneme discrimination study that production training can be helpful for learning to discriminate L2 sounds.…”
Section: Interweaving Accent Production and Accent Comprehensionmentioning
confidence: 99%
“…Kartushina et al. (), in their review of the literature, differentiated between indirect and direct visual feedback. Indirect visual feedback, the focus of this study, consists of providing raw or abstracted acoustic representations.…”
mentioning
confidence: 99%
“…No study to date has specifically addressed the mechanism underlying the relationship between sound‐production accuracy and its variability. Nevertheless, the results of previous studies showing (a) high correlations between production accuracy and variability in L2 speakers (Kartushina & Frauenfelder, ) and novice learners (Kartushina et al., ), (b) a decrease in variability as a result of improvements in production and perception accuracy (Kartushina et al., , ), and (c) a relationship between these two production measures and categorical perception in the L1 (Franken et al., ; Perkell et al., ) suggest that gains in accuracy and compactness in the multiple‐talker group might be mediated by more accurate sound perception.…”
Section: Discussionmentioning
confidence: 95%
“…Such processing might lead to an establishment of more accurate auditory targets, which, in turn, might tune the production, leading to more compact/stable articulatory realizations. Other production‐training studies have shown that training‐related improvements in production were accompanied by a reduction in production variability and also led to small improvements in the perception of the trained sounds (Kartushina et al., ). The results of the current study suggest that hearing multiple talkers during production training encourages participants to disregard irrelevant acoustic information (here, variability in pitch or between‐talker variability) and to focus on the relevant phonetic features (here, F1 and F2), which allows for the two trained categories to be distinguished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation